A cellulose acetate casting liquid, a modified cellulose acetate base film, and preparation method and use thereof

By uniformly distributed carboxymethyl microbeen cellulose in acetic cellulose base membrane, the problem of carbon dot aggregation is solved, the structural strength and detection sensitivity of the detection membrane is improved, and higher environmental stability and reliability are achieved.

CN118515916BActive Publication Date: 2025-01-28UNIV OF SCI & TECH BEIJING
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410512335.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-26
Publication Date
2025-01-28
Estimated Expiration
2044-04-26

AI Technical Summary

Technical Problem

In the prior art, carbon dots are prone to aggregation during the formation of a solid film, resulting in a weakening of fluorescence performance and affecting the sensitivity and reliability of detection.

Method used

By uniformly distributed carboxymethyl microbeen cellulose in acetic cellulose base membrane, the carbon dot is evenly distributed with its adsorption effect to avoid aggregation, thereby improving the structural strength and detection performance of the membrane.

Benefits of technology

The uniform distribution of carbon dots is achieved, and the environmental stability, reliability of the fluorescent detection membrane and the response sensitivity to metal ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118515916B_ABST
    Figure CN118515916B_ABST
Patent Text Reader

Abstract

A modified cellulose acetate base film comprises a three-dimensional network membrane structure formed by cellulose acetate through covalent bonds and hydrogen bonds, and carboxymethyl micro-nanocellulose and carbon dots uniformly distributed in the three-dimensional network membrane structure through hydrogen bonds, and is obtained by tape casting using a cellulose acetate casting solution, wherein the cellulose acetate casting solution comprises 2-8 parts by weight of cellulose acetate, 45-50 parts by weight of dichloromethane, 35-40 parts by weight of methanol, 5-10 parts by weight of water, 1-3 parts by weight of glycerol, 0.1-0.5 parts by weight of a surfactant, 0.05-0.2 parts by weight of carboxymethyl cellulose nanofibers, and 0.004-0.012 parts by weight of carbon dots. The modified cellulose acetate base film of the present invention has high detection sensitivity and high reliability for heavy metal ions in water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of materials, and in particular to a cellulose acetate casting liquid, a modified cellulose acetate base film, and a preparation method and use thereof. Background Art

[0002] With the development of industrialization, heavy metal pollution is becoming more and more serious. Heavy metals are persistently toxic and cannot be degraded when they are enriched in organisms. When they are enriched to a certain extent, they will cause serious damage to organisms. Therefore, rapid and highly sensitive analysis and detection of heavy metal content in media such as water bodies is of great significance for protecting the environment and improving people's quality of life.

[0003] At present, water quality testing methods include atomic spectroscopy, UV-visible spectrophotometry, mass spectrometry, electrochemical method, etc. Although traditional instrumental analysis methods have advantages such as sensitivity and professionalism, they have disadvantages such as expensive instruments, complicated operation steps and long cycles, and strong professionalism of operators. There are also methods that use various functional materials to quickly detect heavy metal content, but liquid, powder and other forms of detection carriers still have disadvantages such as cumbersome on-site detection.

[0004] Thin film materials have the advantages of being easy to carry and quick to detect and have been widely studied. Cellulose acetate is a rare natural polymer derivative material for preparing porous films. The porous network structure membrane has a selectable pore distribution, stable retention performance, high adsorption and high mechanical strength, which is conducive to the retention of pollutants on the membrane and efficient contact with the color developer or fluorescent substance, thereby improving the detection sensitivity. At present, there are many documents and patents reporting on the preparation and molding of cellulose acetate membranes. CN106568751A provides a porous membrane composed of CNTs-modified 1,4# dihydroxyanthraquinone-doped cellulose and its preparation method and application; CN116983840A provides a method for preparing a polylactic acid / cellulose acetate honeycomb composite porous membrane; CN112574466A provides a method for regulating the order of the structure of a porous membrane of a cellulose acetate derivative; CN108359055A provides an ordered porous membrane material of a cellulose acetate graft copolymer and its preparation method. Carbon dots (CDs) are considered to be an ideal fluorescent material and have attracted extensive attention due to their stable fluorescence, high optical absorption, good physicochemical stability, and good biocompatibility. In recent years, the fluorescence quenching effect caused by the interaction between metal ions and fluorophores has been widely studied, and CDs have been proven to be a promising fluorescent sensor for heavy metal ion detection due to their unique size and functional structure.

[0005] However, since carbon dots are nanoparticles, they will aggregate in the process of forming a solid film, resulting in a weakening of the fluorescence performance. This will not only reduce the physical properties of the fiber membrane, but also cause uneven fluorescence and weakened detection response, affecting the sensitivity and reliability of the detection.

[0006] Therefore, how to design a porous base membrane based on uniformly distributed carbon dots to provide a fluorescent detection membrane with greater environmental stability, reliability and strong ion response is an urgent problem to be solved by technicians in this field. Summary of the invention

[0007] One of the purposes of the present invention is to provide a modified cellulose acetate base film in view of the deficiencies in the prior art, using cellulose acetate as a substrate to form a three-dimensional network membrane structure, and evenly distributing carboxymethyl micro-nano cellulose, effectively improving the structural strength of the membrane, and utilizing the adsorption effect of evenly distributed carboxymethyl micro-nano cellulose to ensure that carbon dots are evenly distributed in the three-dimensional network membrane structure, avoiding carbon dot aggregation, ensuring the fluorescence intensity of carbon dots in the base film and the quenching effect on metal ions, and improving the detection sensitivity and reliability of the base film.

[0008] The second object of the present invention is to provide a method for preparing the above-mentioned modified cellulose acetate base film, which has a simple and convenient process. Through step-by-step temperature rising and baking, a high-porosity, three-dimensionally penetrating base film is obtained, thereby ensuring the detection sensitivity and reliability of the base film.

[0009] The technical solution for implementing the present invention is: a cellulose acetate casting solution, comprising the following components in parts by weight:

[0010] 2-8 parts of cellulose acetate;

[0011] 45-50 parts of dichloromethane;

[0012] 35-40 parts of methanol;

[0013] 5-10 parts water;

[0014] 1-3 parts of glycerin;

[0015] Surfactant 0.1-0.5 parts;

[0016] Carboxymethyl micro-nanocellulose 0.05-0.2 parts;

[0017] Carbon dots 0.004-0.012 parts.

[0018] Furthermore, the cellulose acetate is cellulose diacetate with an acetyl content of 37-40%, the carboxymethyl micro-nanocellulose has a diameter of 50-200nm, a length of 100-5000nm, a carboxymethyl substitution degree of 0.9-1.5, the particle size of the carbon dots is 3-5nm, and the surfactant is sodium dodecylbenzene sulfonate.

[0019] The method for preparing any of the above-mentioned cellulose acetate casting solutions comprises the following steps:

[0020] 1) Take materials in proportion;

[0021] 2) taking surfactant, carbon dots, glycerol and carboxymethyl micro-nanocellulose and dissolving them in water;

[0022] 3) Add dichloromethane and methanol, add cellulose acetate under stirring, and continue stirring until it is completely dissolved.

[0023] Preferably, after the addition of cellulose acetate in step 3), stirring is performed in a sealed environment for 3-5 hours.

[0024] A modified cellulose acetate base film comprises a three-dimensional network membrane structure formed by cellulose acetate through covalent bonds and hydrogen bonds, and carboxymethyl micro-nano cellulose and carbon dots uniformly distributed in the three-dimensional network membrane structure through hydrogen bonds.

[0025] Preferably, the thickness of the three-dimensional network structure base film is 0.15-0.25 mm.

[0026] The method for preparing any of the above modified cellulose acetate base films is to obtain the film by casting using any of the above cellulose acetate casting solutions.

[0027] The tape casting comprises the following steps:

[0028] 1) taking the cellulose acetate casting solution of claim 1 or 2, degassing it, scraping it with a scraping machine, and keeping it at 20-30° C. for 15-30 minutes;

[0029] 2) baking by step-wise temperature increase and drying to form a film, thereby obtaining a modified cellulose acetate base film.

[0030] Preferably, the step-by-step heating in step 2) is: 30-40°C for 5-15 min, 40-50°C for 5-15 min, 50-55°C for 5-15 min, preferably, 35°C for 5 min, 45°C for 5 min, 50°C for 5 min.

[0031] The present invention also provides the use of the modified cellulose acetate base membrane in water quality detection.

[0032] Furthermore, the target of water quality detection is heavy metal ions, and the heavy metal ions are Cu 2+ and Hg 2+ , the detection method is:

[0033] 1) Take the modified cellulose acetate base film and soak it in different known concentrations of Cu 2+ and Hg 2+ The solution was taken out and its fluorescence intensity was tested to prepare a standard curve;

[0034] 2) Take the modified cellulose acetate base film, add it into water of unknown concentration according to the soaking method in step 1), take it out and test its fluorescence intensity according to the test method in step 1), and calculate the Cu content in the water of unknown concentration according to the fluorescence intensity. 2+ and Hg 2+ concentration.

[0035] The above technical solution has the following beneficial effects:

[0036] 1. The cellulose acetate casting solution provided by the present invention comprises cellulose acetate, dichloromethane, methanol, water, glycerol, a surfactant, carboxymethyl micro-nano cellulose and carbon dots, wherein cellulose acetate is used as a substrate to form a base film with high porosity, high adsorption performance and high mechanical strength, and carboxymethyl micro-nano cellulose is used as a modified material to improve the structural strength of the base film, which has a negative charge and is evenly dispersed, and attracts positively charged carbon dots to the carboxymethyl micro-nano cellulose to make the carbon dots evenly dispersed; the added dichloromethane and methanol are used as a mixed solvent (dichloromethane is used as a main solvent and methanol is used as a co-solvent) to ensure that the cellulose acetate is completely dissolved, and water is used as a solvent to dissolve the carboxymethyl micro-nano cellulose and the carbon dots, and water and methanol are mutually soluble, thereby ensuring that the cellulose acetate, carboxymethyl micro-nano cellulose and the carbon dots are evenly dispersed in the solvent system, and ensuring that the components are evenly distributed during film formation; the added glycerol is used to improve the hydrophilicity of the film; the added surfactant is used to improve the surface morphology of the film to make its surface smooth.

[0037] 2. The cellulose acetate casting solution provided by the present invention controls the types and proportions of the main solvent, co-solvent and surfactant so that the membrane has a better mesh pore structure and surface flatness.

[0038] 3. The modified cellulose acetate base film provided by the present invention is obtained by casting the above-mentioned cellulose acetate casting liquid, and the main solvent, cosolvent and non-solvent are volatilized in stages by step-by-step temperature drying to form a pore structure. If it is dried at a constant temperature, the main solvent, cosolvent and non-solvent will volatilize at the same time, and the target pore structure cannot be formed. The cellulose acetate in the casting liquid forms a three-dimensional network matrix through covalent bonds and hydrogen bonds, and the added carboxymethyl micro-nano cellulose is evenly distributed in the three-dimensional network matrix through hydrogen bonds. It itself contains a large amount of carboxymethyl and hydroxyl groups. On the basis of improving the mechanical properties of the matrix, it can also establish a strong three-dimensional network structure through hydrogen bonds, providing a larger specific surface area for carbon point distribution and subsequent heavy metal ion detection. In addition, the carboxymethyl micro-nano cellulose is negatively charged, which attracts positively charged carbon points, so that the carbon point particles are evenly dispersed in the matrix to avoid aggregation, which can significantly improve the sensitivity of the detection process.

[0039] The applicant has verified through experiments that the modified cellulose acetate-based membrane prepared by the present invention can reach a recovery rate of 80-120% and a relative standard deviation of <20%, with the recovery rate being used as an indicator for evaluating accuracy and the relative standard deviation being used as an indicator for evaluating precision. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a scanning electron microscope image of the modified cellulose acetate base film prepared in Example 1;

[0041] Figure 2 This is a scanning electron microscope image of the modified cellulose acetate base film prepared in Example 2;

[0042] Figure 3 This is a scanning electron microscope image of the modified cellulose acetate base film prepared in Example 3;

[0043] Figure 4 This is a scanning electron microscope image of the cellulose acetate film prepared in Control Example 1. DETAILED DESCRIPTION

[0044] In the present invention, the reagents used are all commercially available, including cellulose acetate (industrial grade), dichloromethane (analytical grade), methanol (analytical grade), glycerol (analytical grade), ultrafine cellulose powder (industrial grade), and sodium dodecylbenzene sulfonate (analytical grade).

[0045] In the present invention, the unit of parts by weight is gram or kilogram.

[0046] Example 1

[0047] 1) Weigh 0.1 parts by weight of carboxymethyl micro-nanocellulose (degree of substitution DS = 1.33, average diameter 60 nm, length 500-5500 nm), 6 parts by weight of cellulose acetate, 37.7 parts by weight of methanol, 48 parts by weight of dichloromethane, 2 parts by weight of glycerol, 0.2 parts by weight of sodium dodecylbenzene sulfonate, 6 parts by weight of pure water, and 0.006 parts by weight of carbon dots.

[0048] In the first step, sodium dodecylbenzene sulfonate, carbon dots, glycerol and carboxymethyl micro-nanocellulose are dissolved in pure water; in the second step, a mixed solvent of dichloromethane and methanol is added, and cellulose acetate is added while stirring with a magnetic stirrer. When the addition is completed, the beaker is sealed with a sealing film and stirred for 3-5 hours;

[0049] 2) After the casting liquid is static and degassed, adjust the thickness of the scraper and use 800 micron thickness scraper: Pour the clarified solution onto a dry and clean glass plate and quickly scrape the film with the scraper. Wait for the liquid film to undergo phase inversion at room temperature (20-30°C) for 25 minutes, then transfer it to an oven and stepwise increase the temperature at 35°C, 45°C, and 50°C for 5 minutes each. Finally, dry it into a film and remove it from the glass plate to obtain a modified cellulose acetate base film with a length of 20 cm, a width of 10 cm, a thickness of 0.2 mm, and an average pore size of 10 μm.

[0050] 3) The modified cellulose acetate base membrane obtained in step 2) was clamped with tweezers into the 10 mg / l Cu 2+ and Hg 2+ The sample was placed in the solution and removed with tweezers after 60 seconds to remove excess water on the surface. The sample was irradiated with a 365 nm ultraviolet lamp and observed with the naked eye and tested with a fluorescence spectrophotometer for changes in the fluorescence of the test membrane. The fluorescence value of the blank sample was F 0 The fluorescence value measured by detecting the metal ion solution is F.

[0051] Example 1 The scanning microscope image of the modified cellulose acetate base film obtained is as follows Figure 1 As shown. It can be seen that the modified cellulose acetate base membrane has a three-dimensional network-like porous structure with a high porosity. The fracture stress of the modified cellulose acetate membrane is 4.41MPa and the fracture strain is 5.79%. Its fluorescence intensity F 0 37.52 au, Cu detected 2+ The fluorescence intensity F was then 6.76 au, detecting Hg 2+ The fluorescence intensity F was 5.96 au. The quenching efficiency of the detection membrane reached 82% and 85% respectively. 2+ and Hg 2+ The copper ion recovery rate is 91.0% to 120.0%, the relative standard deviation is less than 2.9%, and the mercury ion recovery rate is 91% to 110.0%, and the relative deviation is less than 3.1%.

[0052] Example 2

[0053] 1) Weigh 0.1 parts by weight of carboxymethyl micro-nanocellulose (degree of substitution DS = 1.11, average diameter of 100 nm, length 955-1720 nm), 6 parts by weight of cellulose acetate, 37.7 parts by weight of methanol, 48 parts by weight of dichloromethane, 2 parts by weight of glycerol, 0.2 parts by weight of sodium dodecylbenzene sulfonate, 6 parts by weight of pure water, and 0.006 parts by weight of carbon dots.

[0054] In the first step, sodium dodecylbenzene sulfonate, carbon dots, glycerol and carboxymethylated micro-nanocellulose are dissolved in pure water; in the second step, a mixed solvent of dichloromethane and methanol is added, and cellulose acetate is added while stirring with a magnetic stirrer. When the addition is completed, the beaker is sealed with a sealing film and stirred for 3-5 hours;

[0055] 2) After the casting liquid is static and degassed, adjust the thickness of the scraper, use 800 micron thickness scraper, pour the clarified solution on a dry and clean glass plate, and quickly scrape the film with the scraper. Wait for the liquid film to undergo phase inversion at room temperature (20-30°C), keep it for 25 minutes, then transfer it to an oven, and then transfer it to an oven, step by step increase the temperature at 35°C, 45°C, and 50°C for 5 minutes each, and finally dry it into a film. Remove the film from the glass plate to obtain a modified cellulose acetate base film; the length is 20 cm, the width is 10 cm, the thickness is 0.2 mm, and the average pore size is 8 μm;

[0056] 3) The modified cellulose acetate base membrane obtained in step 2) was clamped with tweezers into the 10 mg / l Cu 2+ and Hg 2+ The sample was placed in the solution and removed with tweezers after 60 seconds to remove excess water on the surface. The sample was irradiated with a 365 nm ultraviolet lamp and observed with the naked eye and tested with a fluorescence spectrophotometer for changes in the fluorescence of the test membrane. The fluorescence value of the blank sample was F 0 The fluorescence value measured by detecting the metal ion solution is F.

[0057] Example 2 The scanning microscope image of the modified cellulose acetate base film obtained is as follows Figure 2 As shown in Figure 2, the fracture stress of the modified cellulose acetate base film is 4.03 MPa and the fracture strain is 4.56%. Its fluorescence intensity F 0 35.09au, Cu 2+ The fluorescence intensity F is then 9.8 au, detecting Hg 2+ The fluorescence intensity F was 6.96 au, and the quenching efficiency of the detection membrane reached 72% and 80%, respectively.

[0058] Example 3

[0059] 1) Weigh 0.1 parts by weight of carboxymethyl micro-nanocellulose (degree of substitution DS = 0.92, average diameter 150 nm, length 300-540 nm), 6 parts by weight of cellulose acetate, 37.7 parts by weight of methanol, 48 parts by weight of dichloromethane, 2 parts by weight of glycerol, 0.2 parts by weight of sodium dodecylbenzene sulfonate, 6 parts by weight of pure water, and 0.006 parts by weight of carbon dots.

[0060] In the first step, sodium dodecylbenzene sulfonate, carbon dots, glycerol and carboxymethylated micro-nanocellulose are dissolved in pure water; in the second step, a mixed solvent of dichloromethane and methanol is added, and cellulose acetate is added while stirring with a magnetic stirrer. When the addition is completed, the beaker is sealed with a sealing film and stirred for 3-5 hours;

[0061] 2) After the casting liquid is static and degassed, adjust the thickness of the scraper, use 800 micron thickness scraper, pour the clarified solution on a dry and clean glass plate, and quickly scrape the film with the scraper. Wait for the liquid film to undergo phase inversion at room temperature (20-30°C), keep it for 25 minutes, then transfer it to an oven, and then transfer it to an oven, step by step increase the temperature at 35°C, 45°C, and 50°C for 5 minutes each, and finally dry it into a film. Remove the film from the glass plate to obtain a modified cellulose acetate base film; the length is 20 cm, the width is 10 cm, the thickness is 0.2 mm, and the average pore size is 5 μm;

[0062] 3) The modified cellulose acetate base membrane obtained in step 2) was clamped with tweezers into the 10 mg / l Cu 2+ and Hg 2+ The sample was placed in the solution and removed with tweezers after 60 seconds to remove excess water on the surface. The sample was irradiated with a 365 nm ultraviolet lamp and observed with the naked eye and tested with a fluorescence spectrophotometer for changes in the fluorescence of the test membrane. The fluorescence value of the blank sample was F 0 The fluorescence value measured by detecting the metal ion solution is F.

[0063] Example 3 The scanning microscope image of the modified cellulose acetate base film obtained is as follows Figure 3 As shown in the figure, the fracture stress of the modified cellulose acetate base film is 3.24 MPa and the fracture strain is 5.27%. 0 33.83 au, Cu 2+ The fluorescence intensity F was then 9.37 au, detecting Hg 2+ The fluorescence intensity F was then 9.45 au. The quenching efficiency of the detection membrane reached 72% and 72% respectively.

[0064] Example 4

[0065] The modified cellulose acetate base film prepared in Example 1 was clamped with tweezers into the prepared Cu 2+ and Hg 2+ The modified cellulose acetate base membrane was placed in the standard solution and removed with tweezers after 60 seconds to remove excess surface water. The fluorescence changes of the modified cellulose acetate base membrane were tested with a fluorescence spectrophotometer.

[0066] The fluorescence value of the blank sample is F 0 The fluorescence value of the standard solution is F.0 / F is the vertical mark, Cu 2+ and Hg 2+ The concentration of the modified cellulose acetate membrane is used as the horizontal axis to obtain the standard working curve. 0 / F=0.292[Hg 2+ ]+1.25, the linear relationship of modified cellulose acetate membrane to copper ion detection: F 0 / F=0.227[Cu 2+ ]+1.06.

[0067] Take a portion of copper-containing wastewater and a portion of mercury-containing wastewater, immerse the modified cellulose acetate membrane prepared in Example 1 in the wastewater for 1 minute, then take it out and test its fluorescence intensity. Calculate the metal ion concentration according to the standard curve equation. Use an ICP spectrometer to test its copper ion and mercury ion concentrations as accurate values.

[0068] The fluorescence intensity of the modified cellulose acetate membrane prepared in Example 1 was measured, and the fluorescence intensity F of the copper-containing wastewater was measured. 1 The fluorescence intensity F after detecting mercury-containing wastewater is 17.34 au. 1 The concentration of copper ion and mercury ion calculated by the curve equation is 4.86mg / l and 1.01mg / l respectively, and the required time is 1min.

[0069] The copper ion and mercury ion concentrations in the two wastewaters tested using an ICP spectrometer were 4.92 mg / l and 0.83 mg / l, respectively, and the time required was 5 minutes.

[0070] Comparative Example 1

[0071] 1) Weigh 6 parts by weight of cellulose acetate, 37.8 parts by weight of methanol, 48 parts by weight of dichloromethane, 2 parts by weight of glycerol, 0.2 parts by weight of sodium dodecylbenzenesulfonate, 6 parts by weight of pure water, and 0.006 parts by weight of carbon dots.

[0072] In the first step, sodium dodecylbenzene sulfonate, carbon dots and glycerol are dissolved in pure water; in the second step, a mixed solvent of dichloromethane and methanol is added, and cellulose acetate is added while stirring with a magnetic stirrer. When the addition is completed, the beaker is sealed with a sealing film and stirred for 3-5 hours;

[0073] 2) After the casting liquid is static and degassed, adjust the film scraping machine thickness, use 800 micron film scraping thickness, pour the clarified solution onto a dry and clean glass plate, and quickly scrape the film with the film scraping machine. Wait for the liquid film to undergo phase inversion at room temperature (20-30°C), keep for 40 minutes, and finally dry into a film. Remove the film from the glass plate to obtain the cellulose acetate water quality test film.

[0074] 3) Use tweezers to clamp the test membrane obtained in step 2) into the 10 mg / l Cu 2+ and Hg 2+ The sample was placed in the solution and removed with tweezers after 60 seconds to remove excess water on the surface. The sample was irradiated with a 365 nm ultraviolet lamp and observed with the naked eye and tested with a fluorescence spectrophotometer for changes in the fluorescence of the test membrane. The fluorescence value of the blank sample was F 0 The fluorescence value measured by detecting the metal ion solution is F.

[0075] The scanning microscope image of the cellulose acetate test membrane obtained in Comparative Example 1 is as follows: Figure 4 As shown, its fracture stress is 2.98MPa and fracture strain is 4.82%. Its fluorescence intensity F 0 24.9 au, detection of Cu 2+ The fluorescence intensity F was then 10.08 au, detecting Hg 2+ The fluorescence intensity F was then 9.27 au. The quenching efficiency of the detection membrane reached 60% and 63%, respectively.

[0076] It can be seen that compared with conventional cellulose acetate membranes, the modified cellulose acetate-based membrane prepared by the present application has higher fluorescence intensity and higher quenching efficiency after contact with metal ions, indicating that the carbon dots on the modified sodium acetate cellulose detection membrane are more evenly distributed, which is beneficial to improving the sensitivity of the water quality detection membrane.

Claims

1. A cellulose acetate casting solution, characterized in that: It includes the following components by weight: Cellulose acetate 2-8 parts; 45-50 parts of dichloromethane; Methanol 35-40 parts; 5-10 parts water; 1-3 parts of glycerol; Surfactant 0.1-0.5 parts; Carboxymethyl micro-nanocellulose 0.05-0.2 parts; Carbon dots 0.004-0.012 parts.

2. The cellulose acetate casting solution according to claim 1, characterized in that: The cellulose acetate is cellulose diacetate with an acetyl content of 37-40%. The carboxymethyl micro-nanocellulose has a diameter of 50-200 nm, a length of 100-5000 nm, a carboxymethyl substitution degree of 0.9-1.5, a particle size of the carbon dots of 3-5 nm, and the surfactant is sodium dodecylbenzene sulfonate.

3. A method for preparing the cellulose acetate casting solution according to claim 1 or 2, characterized in that: The following steps are involved: 1) Take materials in proportion; 2) Take surfactant, carbon dots, glycerol and carboxymethyl micro-nanocellulose and dissolve them in water; 3) Add dichloromethane and methanol, then add cellulose acetate while stirring, and continue stirring until completely dissolved.

4. The preparation method according to claim 3, characterized in that: Step 3) After the cellulose acetate is added, stir in a sealed environment for 3-5 hours.

5. A modified cellulose acetate base film, characterized in that: The invention comprises a three-dimensional network membrane structure formed by cellulose acetate through covalent bonds and hydrogen bonds, and carboxymethyl micro-nanocellulose and carbon dots uniformly distributed in the three-dimensional network membrane structure through hydrogen bonds, and is obtained by tape casting using the cellulose acetate casting solution according to claim 1 or 2.

6. The modified cellulose acetate base film according to claim 5, characterized in that: The thickness of the three-dimensional network structure base film is 0.15-0.25 mm.

7. A method for preparing the modified cellulose acetate base film according to claim 5 or 6, characterized in that: The cellulose acetate film casting solution according to claim 1 or 2 is used to obtain the film by tape casting.

8. The preparation method according to claim 7, characterized in that: The tape casting comprises the following steps: 1) Take the cellulose acetate casting solution of claim 1 or 2, degas, scrape the film with a scraper, and keep it at 20-30°C for 15-30 minutes; 2) Baking and drying the film by step-wise temperature increase to obtain a modified cellulose acetate base film.

9. The preparation method according to claim 8, characterized in that: Step 2) The stepwise heating is as follows: 30-40°C for 5-15 min, 40-50°C for 5-15 min, 50-55°C for 5-15 min.

10. The preparation method according to claim 9, characterized in that: The step-by-step heating is as follows: 35°C for 5 min, 45°C for 5 min, and 50°C for 5 min.

11. Use of the modified cellulose acetate base film according to claim 5 or 6 in water quality testing, wherein the target of the water quality testing is heavy metal ions, and the heavy metal ions are Cu 2+ and Hg 2+ , the detection method is: 1) Take the modified cellulose acetate base membrane and soak it in different known concentrations of Cu 2+ and Hg 2+ The solution was taken out and its fluorescence intensity was tested to prepare a standard curve; 2) Take the modified cellulose acetate base film and add it to water of unknown concentration according to the soaking method in step 1). Take it out and test its fluorescence intensity according to the test method in step 1), and calculate the Cu content in the water of unknown concentration based on the fluorescence intensity. 2+ and Hg 2+ concentration.

Citation Information

Patent Citations

  • CNTs-modified 1,4-dioxyanthraquinone doped cellulose-combined porous membrane and preparation method and application thereof

    CN106568751A

  • Ordered porous cellulose acetate grafted copolymer membrane material and preparation method thereof

    CN108359055A

  • Method for regulating and controlling structural order degree of cellulose acetate derivative porous membrane

    CN112574466A

  • Preparation method of polylactic acid / cellulose acetate honeycomb composite porous membrane

    CN116983840A

  • Modified cellulose acetate ultrafiltration membrane preparation method

    CN102500247A